Prevention of Hypertension through the Use of Homemade Herbs and Supplements - Fujiati, Fujiati; Isnaini, Isnaini; Joharman, Joharman; Audhah, Nelly Al; Asnawati, Asnawati; Hayatie, Lisda; Sari, Annida Permata; Irawanto, Irawanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
Globally, approximately 1.28 billion individuals are affected by hypertension, a Non-Communicable Disease (NCD) that represents the second leading risk factor for premature death. Hypertension raises the risk of cardiovascular disease, a global health challenge. Hypertension can result from a lack of information on the disease. Hypertension can be controlled and prevented at the community level through education, the introduction of antihypertensive plants, and training in herbal supplements. To improve public health in West Martapura, counseling and training sessions were held with the PKK. Visual media, leaflets, and demonstrations were used. The mean posttest scores for knowledge about hypertension prevention and control, knowledge of herbal plants with antihypertensive properties, and knowledge and skills in making health supplements from herbal plants were 90.5, 89.0, and 84.5, respectively.